Sistem Kontrol Kualitas Air pada Akuaponik Ikan Nila dan Cabai Rawit Berbasis Embedded System menggunakan Fuzzy Logic - Satrio Priambodo; Anang Andrianto; Dwiretno Istiyadi Swasono (Faculty of Computer Science, University of Jember, 2022)
Aquaponics is a cultivation method that combines aquaculture and hydroponics which can produce two products, namely plants and fish at a time and on relatively narrow land. The important thing in implementing aquaponics is to maintain water quality so that it remains at the standard of the two products. Automatic water quality control can make it easier for cultivators to maintain water quality more efficiently. Therefore we need an aquaponic water quality control system that focuses on the parameters of dissolved oxygen (DO), total dissolved solids (TDS), and hydrogen power (PH). DO control uses a pump that functions to increase DO levels. TDS control uses a pump that circulates AB mix nutrients to increase TDS and the addition of water volume to lower TDS. PH control uses a pump that circulates PH up and down PH. In its development, the arithmetic method used to process data is fuzzy. The output of this calculation is the duration of time the pump is running. The system is applied to a concrete pond measuring 4 x 1.5 x 1 meter with aquaponic products in the form of 100 fish and 20 cayenne pepper plants.